Advances from the Office of Naval Research STEM Grand Challenge: expanding the boundaries of intelligent tutoring systems - Scotty D. Craig; Arthur C. Graesser; Ray S. Perez (SpringerOpen, 2018)
Abstract This special issue presents evaluations of four intelligent tutoring systems. These systems were funded under the Office of Naval Research's STEM Grand Challenge for intelligent tutoring systems. The systems each represent aspects of how ITS can address STEM education or how aspects of multiple systems can be integrated to support STEM education. The selected papers also provide empirical evidence for the effectiveness of each system. The current paper provides an overview of the Office of Naval Research STEM Grand Challenge program, the systems funded under the program, and summaries of the articles within this special issue.